The Influence of Transformational Leadership and Reward Systems on Employee Performance - Zaenal Abidin; Fuadi; Anis Fuad Salam; Heri Sapari Kahpi (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study was to analyze the transformational leadership and reward system to employee performance. The main task of a leader is to empower, motivate the employees in order to optimize their ability to achieve organizational goals. This research was conducted at the Department of Building Supervision and Control of Jakarta in July and August 2014 the total respondents eighty employees collected by simple random sampling technique. To analyze the data collected, the type of data being analyzed researchers used quantitative data. The method of analysis used in this study is multiple regression analysis in which this analysis can be used to look at the relationship and the influence of transformational leadership and reward system on employee performance at the Department of Building Supervision and Control of Jakarta. The results of the study found that transformational leadership and reward systems have a significant effect on employee performance.